A large receptive–expressive gap in bilingual children - Keller, Karin; Troesch, Larissa M.; Grob, Alexander (Frontiers in Psychology, 2015)
The present study focuses on the discrepancy between receptive and expressive language competence among bilingual children and tests possible explanatory factors of this gap. The sample consisted of 406 bilingual children with German as their second language (L2) and 46 different first languages. Receptive and expressive German language competence (L2) were measured with a standardized language development test at the age of 43 months. As expected, a significant gap in receptive and expressive German language competence (L2) emerged in all language groups. The size of the gap reached one standard deviation and correlated with the amount of language contact and thus provides support for the language exposure hypothesis. However, we found no evidence for the language familiarity hypothesis. The present study contributes to the understanding of mechanisms in bilingual language development and, hence, is consequential for both basic research and language assessment practice.